Global endothelial function assessment using pulse wave analysis in hypercholesterolemia - Nik Ibrahim, Nik Nor Izah (2022)
To compare global endothelial function assessed by pulse wave analysis (PWA) using the ratio of endothelium dependent vasodilatation (EDV) to endothelium independent vasodilatation (EIV) in patients with hypercholesterolemia and controls. 92 subjects [46 hypercholesterolemics, 46 controls] were studied at standardized conditions. Baseline augmentation index (AIx) was assessed followed by the administration of 0.5 mg sublingual nitroglycerine, an endothelium independent vasodilator. AIx was assessed and the maximum change in AIx after nitroglycerine was recorded as EIV. After a washout period of 30 minutes, 400 µg of inhaled salbutamol, an endothelium dependent vasodilator was administered. AIx was assessed again and the maximum change in AIx after salbutamol was recorded as EDV. Global endothelial function was calculated as EDV:EIV ratio. EDV and EIV in patients with hypercholesterolemia compared to controls were 2.97 ± 3.95 and 6.65 ± 3.80 (p<0.001); and 13.41 ± 4.57 and 15.88 ± 4.78 (p=0.01) respectively. EDV:EIV ratio was significantly reduced in patients with hypercholesterolemia compared to controls; 0.21 ± 0.38 and 0.44 ± 0.24 (p<0.001) respectively. EDV:EIV ratio was significantly reduced in patients with hypercholesterolemia compared to controls. PWA is a potential clinical tool to assess global endothelial function in patients with hypercholesterolemia.